Depression and Compliance of Fe Tablet Consumption are Combined Risk Factors for Pregnant Women Constipation at Public Health Center Pedurenan, Tangerang City - Putri Ayu Anjani; Khairizka Citra Palupi; Mertien Sa’pang; Dudung Angkasa; Vitria Melani (Journal of Nutrition Science, 2021)
Constipation marked by feces hard one, dry, and difficult issued. About 73.9% pregnant women experience constipation. Increase in the hormone progesterone for pregnant women resulted in drop motility gastrointestinal tract. Constipation affects psychology and causes swelling of the rectum area.To determine the relationship between the level of fiber adequacy, to consumption of Fe tablets and depression and to see the combined risk factors for depression and adherence to consumption of Fe tablets with the incidence of constipation in pregnant women. Design this research is observational analytics with Cross Sectional design. The sample of pregnant women is 55 people with purposive sampling data collection technique. Taking data done with use questionnaire. Statistic test used the chi-square test. 58.2% of pregnant women experienced constipation; 92.7% insufficient fiber sufficiency level; 40.0% adhered to consuming Fe tablets; 55.4% experienced depression; 23.6% of depression was adherent. The results of the chi-square test showed that there was no significant relationship between the level of fiber adequacy and the incidence of constipation in pregnant women (p = 0.298) and a significant relationship with the incidence of constipation in pregnant women, namely consuming Fe tablets (p = 0.039; OR = 4.080), depression (p = 0.026; OR = 4.125), risk factors for the combination of depression and adherence to consumption of Fe tablets (p = 0.005).Compliance with Fe tablet consumption and depression can increase the risk of constipation in pregnant women by 4,080 times and 4,125 times.